Opportunities and Challenges for "Karang Taruna" as a Human Service Organization to Strengthening KUBE's Management - Sariningsih, Yuce; Gunawan, Uga Pratama; Inayah, Fathiya Nur (Journal of Economic Empowerment Strategy (JEES), 2024)
Karang Taruna is a voluntary youth organization that focuses on the growth and development of social welfare businesses, productive economic businesses, recreation, sports and the arts. One of  the important goal is to develop the spirit of social entrepreneurship in the younger generation towards independence in their efforts improving social welfare, however, this goal has not been achieved yet, Karang Taruna requires a strategy. This study used qualitative research methods to find out: 1) How is the management of the youth organization; 2) What are the strengths, weaknesses, opportunities and threats; 3) What is the strategy for their developing and implementing youth activities. The research finding showed that it is necessary to implement a strategy to improve KUBE management as a matrix result of weakness and opportunity factors. The weakness of Karang Taruna is that the purpose of developing entrepreneurial activities has not been achieved yet, and the other side there is an opportunity to develop entrepreneurship through Business Group (KUBE) management intervention to improve its performance. KUBE is a kind of social assistance program for underprivileged people by forming micro mini enterprises so that they can become economically empowered.